1989
DOI: 10.1136/jmg.26.4.260
|View full text |Cite
|
Sign up to set email alerts
|

The recurrence risks for mild idiopathic mental retardation.

Abstract: SUMMARY A genetic study of children attending ESN(M) schools in Coventry has shown a recurrence risk of idiopathic mental retardation in sibs lying between 1 in 4 and 1 in 5. There was also a prevalence of mental retardation in other relatives that was greater than the population prevalence, and was less for second degree relatives than for first degree, and less still for third degree relatives. Recurrence in sibs was greater if more than one first degree relative was affected. There was no suggestion of a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
19
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 11 publications
7
19
0
Order By: Relevance
“…The higher prevalence of mental retardation in siblings of the MR group in this study is similar to those of Bundey et al [31] who also observed that the risk was higher the greater the degree of closeness to the index case. Hagberg et al [32] found that 29% of the untraceable causes of mildly mentally retarded children (IQ 50 to 70) had familial predisposition -"close relative with below average intelligence.…”
Section: Discussionsupporting
confidence: 80%
“…The higher prevalence of mental retardation in siblings of the MR group in this study is similar to those of Bundey et al [31] who also observed that the risk was higher the greater the degree of closeness to the index case. Hagberg et al [32] found that 29% of the untraceable causes of mildly mentally retarded children (IQ 50 to 70) had familial predisposition -"close relative with below average intelligence.…”
Section: Discussionsupporting
confidence: 80%
“…It is generally preferable to defer assignment of a specific diagnosis rather than to establish an incorrect diagnosis. Valuable information regarding timing of the insult and the likely recurrence risk may sometimes be inferred in the course of a thorough evaluation, even in the absence of a specific causal diagnosis [Bartley and Hall, 1978;Bundey, 1989].Several approaches strongly influence the diagnostic yield in the evaluation of an individual with MR. Most importantly, the participants wished to stress the importance of serial evaluations of an individual over time.…”
mentioning
confidence: 99%
“…It should be noted that one study failed to find a significant impact of X-linked genes in 'mild idiopathic MR', apart from fragile X. 8 If monogenic XLMR was to account for an excess of 30% of mentally retarded males over females, and forgetting the case where XLMR can lead to MR, albeit generally milder, in females (as in fragile X syndrome), or even leads to MR almost exclusively in females, such as for Rett syndrome, one would expect that 23% of MR in males is caused by XLMR. As discussed by Stevenson et al, 1 several clinical studies reported that XLMR accounts only for 5 -8% of male MR, but it is possible that nonsyndromic XLMR was underestimated in such studies, since it cannot be diagnosed in sporadic cases.…”
mentioning
confidence: 99%